College major peer effects and attrition from the sciences - Marc Luppino; Richard Sander (IZA Journal of Labor Economics, 2015)
This paper examines how peer quality within distinct college majors affects graduation rates and major persistence. To mitigate the selection problem, we control for school-specific fixed effects, as well as very flexible application-admissions pattern fixed effects. Non-science peer quality appears to have a positive effect on both the likelihood that a student chooses a science major and on his or her cumulative GPA. Conversely, students who attend campuses with stronger peers in the sciences are less likely to graduate with a science degree. Weaker, non-minority students typically react to stronger peers in the sciences by shifting majors. Under-represented minorities tend to persist in the sciences regardless of peer quality, but in more competitive programs they suffer - often substantially - in terms of college grades and the likelihood of graduating.
Keywords: I21; J24; 330; College major choice; Mismatch; Peer Effects